Attenuated Mutants of Ehrlichia chaffeensis Induce Protection against Wild-Type Infection Challenge in the Reservoir Host and in an Incidental Host - Nair, Arathy D. S. (Infect Immun, 2015)
Ehrlichia chaffeensis, a tick-borne rickettsial organism, causes the disease human monocytic ehrlichiosis. The pathogen also causes disease in several other vertebrates, including dogs and deer. In this study, we assessed two clonally purified E. chaffeensis mutants with insertions within the genes Ech_0379 and Ech_0660 as vaccine candidates in deer and dogs. Infection with the Ech_0379 mutant and challenge with wild-type E. chaffeensis 1 month following inoculation with the mutant resulted in the reduced presence of the organism in blood compared to the presence of wild-type infection in both deer and dogs. The Ech_0660 mutant infection resulted in its rapid clearance from the bloodstream. The wild-type infection challenge following Ech_0660 mutant inoculation also caused the pathogen's clearance from blood and tissue samples as assessed at the end of the study. The Ech_0379 mutant-infected and -challenged animals also remained positive for the organism in tissue samples in deer but not in dogs. This is the first study that documents that insertion mutations in E. chaffeensis that cause attenuated growth confer protection against wild-type infection challenge. This study is important in developing vaccines to protect animals and people against Ehrlichia species infections.